"WHICH ONE SHOULD I CHOOSE, A GLP-1RA OR A SGLT2 INHIBITOR? OR MAYBE BOTH?''. A POOLED ANALYSIS OF CARDIOVASCULAR OUTCOME TRIALS. (June 2022) - Patoulias, Dimitrios; Katsimardou, Alexandra; Toumpourleka, Maria; Imprialos, Konstantinos; Stavropoulos, Konstantinos; Karagiannis, Asterios; Papadopoulos, Christodoulos; Doumas, Michael
Abstract : Objective: Glucagon-like peptide 1 receptor agonists (GLP-1RAs) and sodium–glucose cotransporter 2 (SGLT2) inhibitors are prioritized for the treatment of patients with type 2 diabetes mellitus (T2DM) to reduce major adverse cardiovascular events (MACE), hospitalization for heart failure (HF), cardiovascular death, or chronic kidney disease (CKD) development and progression, regardless of glycemic control. A question that inevitably arises is whether these drug classes can be combined in clinical practice, and if there is a synergistic cardio-protective effect with such a combination. Design and method: We sought to determine whether the SGLT-2 inhibitor/GLP-1RA combination confers or not a greater risk reduction on "hard'' cardiovascular outcomes, compared to each drug class alone, by pooling relevant data from intention to treat analyses of the relevant cardiovascular outcome trials. We set as primary efficacy outcome the occurrence of a major adverse cardiovascular event (MACE), defined as the composite of cardiovascular death, non-fatal myocardial infarction, non-fatal stroke, and as secondary efficacy outcome the occurrence of hospitalization for HF. Results: Concerning the primary efficacy outcome, we showed that treatment with SGLT-2 inhibitor/GLP-1RA combination compared to GLP-1RA/placebo resulted in a non-significant decrease in the risk for MACE (RR = 0.89, 95% CI; 0.67 – 1.19, I2 = 0%). When we compared treatment with SGLT-2 inhibitor/GLP-1RA combination with SGLT-2 inhibitor/placebo combination, we demonstrated again a non-significant effect in the risk for MACE (RR = 0.87, 95% CI; 0.68 – 1.10, I2 = 0%). Regarding the secondary efficacy outcome, treatment with SGLT-2 inhibitor/GLP-1RA combination conferred a significant risk reduction by 71% (RR = 0.29, 95% CI; 0.13 – 0.65, I2 = 5%), compared to GLP-1RA/placebo combination. In addition, a similarly significant decrease by 66% was shown for the SGLT-2 inhibitor/GLP-1RA combination compared to SGLT-2 inhibitor/placebo combination (RR = 0.34, 95% CI; 0.15 – 0.76, I2 = 0%). Conclusions: SGLT-2 inhibitor/GLP-1RA combination is not superior to SGLT-2 inhibitor or GLP-1RA monotherapy treatment for the prevention of MACE. However, subjects with HF might benefit from such a combination, since that combination is associated with a significant decrease in the risk for HF hospitalization, ranging from 66 to 71%.